PENGARUH RASIO PROFITABILITAS TERHADAP RETURN SAHAM PERUSAHAAN FARMASI Tbk (STUDI MASA PANDEMI COVID-19) TAHUN 2019 – 2020 - Fani Indriany; Dwi Lesno Panglipursari (Fakultas Ekonomi dan Bisnis Universita Wijaya Putra Surabaya, 2023)
This study aims to examine and analyze the effect of profitability ratios on stock returns of pharmaceutical companies tbk (study during the covid-19 pandemic). The population used in this study were 11 companies, and the sample was 10 companies using purposive sampling technique through the criteria set by the author. The analysis used is multiple linear regression analysis method and data analysis is performed using statistics with SPSS tools. Based on the partial test results, Return On Assets (ROA) has a significant negative effect on Stock Return, Return On Equity (ROE) has a significant positive effect on Stock Return, and Net Profit Margin (NPM) has an insignificant positive effect on Stock Return. Meanwhile, the results of the simultaneous test show that the variables Return On Assets (ROA), Return On Equity (ROA), and Net Profit Margin (NPM) simultaneously have a significant effect on Stock Return of Pharmaceutical Companies Tbk.